Understaffed Home Nursing and Wellbeing of Families of Children with Medical Complexity - S. Margaret Wright; Brian Lee; Leslee T. Belzer; Emily J. Goodwin; Jeffrey D. Colvin (Children)
Background/Objectives: Some children with medical complexity (CMC) require home nursing (HN) to maintain their health, but many families have difficulty staffing approved HN hours. Little is known about the relationship between understaffed HN, the acute care encounter rate, and family wellbeing. This study examined the association between understaffed HN, acute care encounters, and family wellbeing among CMC. Methods: We completed a cross-sectional survey study of caregivers of CMC age 0–17 years at a children’s hospital in the Midwest US. The primary predictors were the proportion of staffed to approved HN hours and the acute care rate. The primary outcome was family wellbeing, measured as parental stress, family impact, interpersonal support, parental empowerment, and financial hardship. General linear models were used to model continuous family wellbeing outcomes. Poisson models were used to calculate the financial hardship summed score ([0–4]). Results: Receipt of <50% of approved HN hours was associated with family financial hardship in adjusted analyses. Total family impact and health-related quality of life (HRQL) scores were associated with the acute care rate, with more positive scores among CMC within the middle tertile for the acute care rate compared to the lowest tertile. There was no association between HN staffing and family wellbeing, or between acute care rate and family financial hardship. Conclusions: High levels of financial hardship were significantly associated with understaffed HN hours. Family impact and parental HRQL were associated with the acute care rate. Access to HN services carries potential family-level and system-level benefits for this complex and high acuity pediatric population.